The university students' perception towards the use of Kadazandusun language in Malaysia - Soon Chiow Thai; Alice Alim Yukin (Asian Scholars Network, 2024)
The Kadazandusun language is the language of the largest indigenous groups in Sabah, Malaysia. This study applied Spolsky’s theory of language management (2004, 2009) to study the perception of the university students towards the usage of Kadazandusun language in Malaysia. The language ideology, language practice and language management are three important independent and interrelated components in theory of language management (Spolsky, 2009). One of the local universities in Malaysia served as the research site of the study. A survey using e-questionnaire was conducted. 37 year-one undergraduate students were the respondents of the study. The findings of the study showed that: i) more than 80 percent of the students would like to learn the languages from oversea ii) about 80 percent of student respondents perceived the Kadazandusun language as the language reflecting the Kadazandusun’s ethnicity identity, iii) by learning the Kadazandusun language will ease the respondents to interact with Kadazandusun communities and iv) the Kadazandusun language is most used as the verbal communication language in the public domain. The researchers of the study suggest that the visibility of the written Kadazandusun language to be improved to upgrade the use of written language in the country.